Development of IoT-Based Breeding and Feed Management Application with Design Thinking Approach in Sheep Farming Industry (Case Study of PT. Agro Surya Perkasa) - Sasongko, Heru; Noviaristanti, Siska (Asian Journal of Management Analytics, 2025)
This study explores the development of an IoT-based application for breeding and feed management in sheep farming using the Design Thinking approach, with a case study at PT Agro Surya Perkasa. A qualitative-descriptive method was used, applying five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test. Data were obtained through interviews, field observations, and literature review involving experienced farmers, livestock managers, and IoT experts. The results show that the application addresses key challenges in breeding and feed efficiency through practical features such as breeding reminders, feed tracking, and health monitoring. The study demonstrates the potential of IoT to enhance livestock productivity and sustainability, offering valuable insights and a reference for similar innovations in other livestock sectors.